2017
DOI: 10.3892/or.2017.5667
|View full text |Cite
|
Sign up to set email alerts
|

Arctigenin inhibits triple-negative breast cancers by targeting CIP2A to reactivate protein phosphatase 2A

Abstract: Abstract.We have shown that a novel STAT3 inhibitor arctigenin (Atn) induces significant cytotoxicity in triple-negative breast cancer (TNBC) cells. This study further delineated molecular mechanisms where by Atn triggered cytotoxicity in TNBC cells. We found Atn can also inhibit metastasis in TNBC cells through cancerous inhibitor of protein phosphatase 2A (CIP2A) pathway. CIP2A is an endogenous inhibitor of protein phosphatase 2A (PP2A), which can increase the migration and invasion of various cancer cells. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 27 publications
(25 reference statements)
3
10
0
Order By: Relevance
“…PP2A, a serine/threonine‐specific phosphatases of multiple oncogenic signaling proteins in cells, is down‐regulated in various cancer cells, and a promising therapeutic target for cancer treatment . Reactivation of PP2A can suppress many cancer cell proliferation and tumor growth . In our experiments, we found that knockdown of PP2A reversed the miR‐21 inhibitor‐induced osteosarcoma cell viability, migration, and invasion inhibition, which implied that ASBEL and miR‐21 promoted osteosarcoma cell viability, migration, and invasion by down‐regulation of PP2A.…”
Section: Discussionsupporting
confidence: 49%
“…PP2A, a serine/threonine‐specific phosphatases of multiple oncogenic signaling proteins in cells, is down‐regulated in various cancer cells, and a promising therapeutic target for cancer treatment . Reactivation of PP2A can suppress many cancer cell proliferation and tumor growth . In our experiments, we found that knockdown of PP2A reversed the miR‐21 inhibitor‐induced osteosarcoma cell viability, migration, and invasion inhibition, which implied that ASBEL and miR‐21 promoted osteosarcoma cell viability, migration, and invasion by down‐regulation of PP2A.…”
Section: Discussionsupporting
confidence: 49%
“…This is consistent with the report that ATG increased cisplatin sensitivity in non-small cell lung cancer cells [21]. Furthermore, several studies showed that ATG suppresses chemical-induced metastatic potential in breast cancer cells, induces cell death of triple-negative breast cancer cells and has no significant toxicity less than 6 mg/kg in beagle dongs [20,65,66]. Anticancer drugs, such as doxorubicin, cisplatin, etc., have various side effects.…”
Section: Discussionsupporting
confidence: 90%
“…Regarding the role of targeting CIP2A towards the treatment of breast cancer, the results of previous studies confirmed that Arctigenin inhibits triple-negative breast cancers proliferation, progression and invasion by targeting CIP2A to reactivate protein phosphatase 2A [48]. Moreover, CIP2A mediate bortezomib-induced apoptosis in TNBC cells.…”
Section: Discussionmentioning
confidence: 82%